2015
DOI: 10.1038/ismej.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Marine diatom proteorhodopsins and their potential role in coping with low iron availability

Abstract: Proteorhodopsins (PR) are retinal-binding membrane proteins that function as light-driven proton pumps to generate energy for metabolism and growth. Recently PR-like genes have been identified in some marine eukaryotic protists, including diatoms, dinoflagellates, haptophytes and cryptophytes. These rhodopsins are homologous to green-light-absorbing, ATP-generating PRs present within bacteria. Here we show that in the oceanic diatom Pseudo-nitzschia granii, PR-like gene and protein expressions increase appreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 12 publications
6
101
2
Order By: Relevance
“…This is consistent with rhodopsin being undetected in sequenced Thalassiosira spp. transcriptomes (Marchetti et al, 2015) and supports the notion that Pseudo-nitzschia may have a competitive advantage over non-rhodopsin containing taxa, allowing for an Fe-independent alternative to photosynthesis for ATP generation during times of Fe stress. Ferritin (FTN) gene expression patterns furthermore diverged between the two taxa at the coastal sites C4 (Line-P) and C2 (CUZ).…”
Section: Fe-related Gene Expression Responses Between Diatom Taxasupporting
confidence: 58%
See 1 more Smart Citation
“…This is consistent with rhodopsin being undetected in sequenced Thalassiosira spp. transcriptomes (Marchetti et al, 2015) and supports the notion that Pseudo-nitzschia may have a competitive advantage over non-rhodopsin containing taxa, allowing for an Fe-independent alternative to photosynthesis for ATP generation during times of Fe stress. Ferritin (FTN) gene expression patterns furthermore diverged between the two taxa at the coastal sites C4 (Line-P) and C2 (CUZ).…”
Section: Fe-related Gene Expression Responses Between Diatom Taxasupporting
confidence: 58%
“…Transcripts for the proton-pumping protein rhodopsin (RHO) furthermore demonstrated differences in expression patterns among genera. This protein can supplement Feintensive photosynthesis in the light-driven production of membrane proton gradients and ATP in some diatoms (Marchetti et al, 2015). Rhodopsin was not detected in Thalassiosira at any location while its expression increased in Pseudo-nitzschia by >2-fold in the DFB/Ctl treatments relative to the Fe treatment at the two lowest dFe sites [C3 (p = 0.01) and O5; Figure 5; Supplementary Table 1].…”
Section: Influence Of Fe Availability On Fe Metabolismmentioning
confidence: 99%
“…Total iron was added as FeEDTA chelates. Trace metal clean techniques were implemented while preparing the Aquil medium and during handling of cultures (Marchetti et al ). All prepared Aquil media were allowed to equilibrate overnight before experimental use.…”
Section: Methodsmentioning
confidence: 99%
“…Further exploration of genomes and transcriptomes from isolated phytoplankton from different seas revealed rhodopsin expression in a wide variety of phytoplankton species (155). Indeed, laboratory experiments showed that the rhodopsin gene and protein expression in the open ocean diatom Pseudo-nitzschia granii UWOSP1E was regulated by iron, with highest levels under iron-limited growth (155). The authors thus conjectured that rhodopsins could "influence carbon cycling indirectly by maintaining seed populations of PR-containing diatoms under chronic iron stress.…”
Section: Proton-pumping Rhodopsins In Chlorophyll-containing Microbesmentioning
confidence: 99%
“…These findings resulted from studies investigating adaptations of phytoplankton to iron deficiency in the surface ocean, where the independency of rhodopsins from iron cofactors, in contrast to chlorophyll reaction centers, might provide a selective advantage. Further exploration of genomes and transcriptomes from isolated phytoplankton from different seas revealed rhodopsin expression in a wide variety of phytoplankton species (155). Indeed, laboratory experiments showed that the rhodopsin gene and protein expression in the open ocean diatom Pseudo-nitzschia granii UWOSP1E was regulated by iron, with highest levels under iron-limited growth (155).…”
Section: Proton-pumping Rhodopsins In Chlorophyll-containing Microbesmentioning
confidence: 99%